Revocation of Will and Judicial Proceedings for Declaring a Will Ineffective Under the Law on Inheritance of Serbia With Reference to Other Contemporary European Legal Systems - Vidić Trninić, Jelena (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
The revocation of a will is a kind of disposition of the mortis causa, by which the previously valid will is completely or partially revoked. The subject of this paper is the analysis of the solutions contained in the Law on Inheritance of Serbia, which primarily concern the way in which this type of disposition of will may be realized. At the same time, the author reviews the legal regulations dedicated to the revocation of wills in other legal systems in Europe. The author finds that in the realization of the right to revoke a will, the legislation of Serbia undoubtedly affirms the freedom of will, and that in that respect, it is in principle harmonized with the legal solutions observed on European legal soil. The author further believes that certain solutions observed in comparative law, such as the revocation by operation of law should be covered by regulations in Serbian inheritance law as well. Finally, according to the author, some existing legal solutions dedicated to the revocation of wills, need to be specified and completed de lege ferenda, in order to achieve legal certainty.